Decoupling from the East Toward the West? : Analyses of Spillovers to the Baltic Countries. (IMF Working Papers; Working Paper ;, 2009)
This paper uses VAR models to examine the magnitude and sources of growth spillovers to the Baltics from key trading partners, as well asfrom the real effective exchange rate (REER). Our results show there are significant cross-country spillovers to the Baltics with those from the EU outweighing spillovers from Russia. Shocks to the REER generally depress growth in the Baltics, and this intensifies over time. We also find that financial and trade channels dominate the transmission of spillovers to the region which partly explains the realization of downside risks to the Baltics from the global slowdown.